Muscle synergies and metabolic adaptations during perturbed walking in older adults - Samuel D’Emanuele; Marco Ghislieri; Laura Ghiotto; Francesca Morra; Lorenzo Budel; Doriana Rudi; Simone Bettega; Gennaro Boccia; Federico Schena; Cantor Tarperi (Scientific Reports)
Abstract Walking is an accessible and beneficial form of physical activity for older adults. However, when performed under perturbed conditions, it can place greater demands on both neuromuscular control and metabolic efficiency, highlighting the need to better understand the underlying adaptations. We compared stable and perturbed walking on a treadmill at three different speeds in 16 healthy older adults. Muscle synergies were extracted from electromyographic signals of eight lower limb muscles, oxygen uptake (VO2), minute ventilation, heart rate, and rate of perceived exertion (RPE) were also collected. Perturbed walking at 3 km/h increased oxygen uptake (p = 0.003; d = -0.52) and energetic cost (EC; p = 0.003; d = -1.12) compared to the stable condition. VO2 (p < 0.001; $$\:{η\:}_{p}^{2}$$ = 0.92), EC (p = 0.02; $$\:{η\:}_{p}^{2}$$ = 0.25) and RPE (χ2 = 4.45; p = 0.04) were higher at 3 km/h than at higher speeds. Four muscle synergies were required to accurately model the neuromuscular control during both conditions. Full-width at half maximum revealed that the transition from stable to perturbed walking led to statistically significant modifications in gait synergy composition (p = 0.01; $$\:{η\:}_{p}^{2}$$ = 0.04). Weight sparsity revealed no significant differences between conditions. These results suggest that the transition from an accurate to a more robust locomotor control for managing continuous perturbations may come at the expense of increased metabolic demand.